Biological activities and health-promoting effects of Pyracantha genus: a key approach to the phytochemical's potential - Sharifi-Rad, Javad; Taheri, Yasaman; Ayatollahi, Seyed Abdulmajid; Naderi, Nima; Kumar, Nanjangud Venaktesh Anil; Koirala, Niranjan; Khadka, Sujan; Karazhan, Natallia; Shahinozzaman, Md; Sen, Surjit; Acharya, Krishnendu; Dey, Abhijit; et al. (Cellular and Molecular Biology, 2020)
Pyracantha spp. are commonly called firethorn, and attract human attention due to their colorful berries. These berries are eaten globally as a traditional remedy for treating different stomach abnormalities, and as a cooking ingredient for folk diets. The present review aims to provide an overview on Pyracantha genus' geographical distribution and botanical description, traditional uses, phytochemical composition, biological activities and safety issues. Several biological activities have been reported to Pyracantha species, namely antioxidant, anti-inflammatory, antimicrobial, larvicidal and cytotoxic properties, most of them attributed to the use of their fruits. Pyracantha species phytochemical composition reveal the presence of interesting bioactive molecules, such as pyracrenic acid and fortuneanosides. The currently reported biological activities to these plants derive from in vitro and in vivo studies, so that clinical trials are needed to confirm these preclinical results. Nonetheless, Pyracantha species can be suggested as a safe herb useful to develop future drug formulations and functional foods.